Integrating Mycorrhizal Fungi with Different Doses of Fertilizer in Nutrient Management for Sustainable Rice Ecosystems - Bharti, Uma; Srivastwa, Pawan Kumar; Kumar, Mukul; Kalyani, Suman; Kumar, Ranvir (Research Perspectives of Microbiology and Biotechnology Vol. 9, 2025)
Arbuscular mycorrhizal fungi play a vital role in a wide range of functions from stress reduction to bioremediation in soils polluted with heavy metals. In this situation, it is important to focus on the combined use of both organic and inorganic fertilizers in judicious combination based on soil nutrient status to improve and sustain the soil fertility and productivity which is called integrated nutrient management. The word “sustainability” has recently come to find itself pushed forward into the limelight and attached as a modifier to nouns with which it formerly had no more than a nodding acquaintance. “Sustainable development,” for example, has been with us for some time, but more recent pairings are now commonplace: sustainable agriculture, sustainable design, sustainable energy, sustainable tourism, and sustainable living, to name a few. Remind of sustainability my research works carried out to solve this problem to save sustainable development. An experiment was conducted during the rainy (Kharif) season in 2015, to find out the effect of fungal isolates with different doses of fertilizer on the growth yield attributes of rice. Vesicular-arbuscular mycorrhiza (VAM) from water samples and cultured from soil samples were examined microscopically for identification on the basis of morphological characters. The experiment comprises three replications and seven treatment combinations. The rice variety–PB1509 was transplanted with a pot experiment. The results showed that application of T1 (N0 P0 K0) (control), T2 (N P K), T3 (N¾ P¾ K), T4 (N½ P½ K), T5 (N½ P½ K + VAMV-SI/4), T6 (N½ P½ K + VAMV-SII/5) and T7 (N½ P½ K+ VAM-SIII/3) gave significantly yield attributes were also higher in this treatment (T5) over control and other treatments. The study concluded that VAM can increase the physiologically activity root system of plants and help in the uptake of N, P, and K nutrients, and water. These findings suggested that the use of VAM may be a boon for the farmers who are destined to grow cereal.